Platform ecosystems as meta‐organizations: Implications for platform strategies - Kretschmer, Tobias; Leiponen, Aija; Schilling, Melissa; Vasudeva, Gurneeta (Strategic Management Journal, 2022)
Abstract Research summary Platform ecosystems have spurred new products and services, sparked innovation, and improved economic efficiency in various industries and technology sectors. A distinctive feature of the platform architecture is its modular and interdependent system of core and complementary components bound together by design rules and an overarching value proposition. Accordingly, we conceptualize platforms as meta‐organizations, or “organizations of organizations” that are less formal and less hierarchical structures than firms, and yet more closely coupled than traditional markets. To function successfully, however, platforms require coordination among multiple participants not all of whose interests are aligned. These organizational features of platforms raise many interesting and complex strategic challenges and hold implications for how platforms compete. In this paper, we discuss some of the most salient features of platform ecosystems as meta‐organizations, specifically in terms of the sources of authority or power in the ecosystem, the motivation and incentives a platform creates to attract participants, and its governance and coordination structures. We then consider how papers appearing in this special issue inform us about the effects of these features on platform competition along three distinct dimensions: (a) with traditional incumbents as platforms enter and establish themselves in new markets, (b) with other platforms to secure an advantageous market position, and (c) with the different participants on the platform to share the value that has been created jointly. We close by identifying some promising directions for future research. Managerial summary Platform ecosystems have spurred new products and services, sparked innovation, and improved economic efficiency in various industries and technology sectors. A distinctive feature of the platform architecture is its modular and interdependent system of core and complementary components bound together by design rules and an overarching value proposition. This makes platform ecosystems an organizational form on its own (a “meta‐organization”), neither possessing the hierarchical instruments of a firm, nor the largely uncoordinated decisionmaking of markets. Successful platform ecosystems require coordination among multiple participants with possibly conflicting interests. We discuss some of the most salient features of platform ecosystems as meta‐organizations, specifically in terms of the sources of authority or power in the ecosystem, the motivation and incentives a platform creates to attract participants, and its governance and coordination structures. These features affect how platform ecosystems compete: i) with a traditional incumbent, ii) with other platform ecosystems, and iii) between different participants of the same platform ecosystem. The articles published in this special issue speak to different aspects of platform competition from the perspective of organization design.